The Impact of Work Engagement and Occupational Stress on Nurse Turnover Intention in Acute Care Hospitals - Saheba Javaid Akhter; Shaikh Muhammad Fakhre Alam Siddiqui; Hammad Zafar (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2025)
Acute care hospital nurse turnover is an important problem that affects patient care, operational efficiency and the overall healthcare outcome. Factors like work engagement and occupational stress can often cause high turnover rates. Previous research in the western context has shown that work engagement is negatively associated with turnover intention and occupational stress is positively related to it, but research in developing countries is scant. Work engagement and occupational stress are investigated as antecedents of turnover intention among nurses in acute care hospitals in Pakistan. Data were collected from 100 nurses using a quantitative approach via a structured survey. Here we analyse the results using Partial Least Squares Structural Equation Modelling (PLS-SEM), and find that work engagement significantly decreases turnover intention and occupational stress significantly increases it. These findings are relevant to the importance of creating a work engaged environment and management of occupational stress in order to increase nurse retention. The results are also useful for healthcare administrators developing retention strategies that will create a supportive work environment that will increase engagement and reduce stress.